Protective Effects of Premna serratifolia L. Leaf Extract Against Gentamicin-Induced Nephrotoxicity in ICR Mice - Josel D. Cruz; Glen S. Nolasco; John Dave A. Dicuangco; Lourdes Fatima S. David (Journal of Healthcare and Biomedical Science, 2024)
Many therapeutic drugs, including aminoglycosides, are known to cause nephrotoxicity and impair kidney function. Gentamicin is a type of aminoglycoside commonly used to treat infection caused by gram-negative bacteria, but it can induce nephrotoxicity by accumulation in the proximal convoluted tubules, resulting in stress, degeneration, and injury to the kidney. Although traditional treatments are limited, natural products, such as in Premna serratifolia, have potential for ameliorative bioactivities. This study examined the nephroprotective effects of P. serratifolia ethanolic leaf extract (PSELE) against gentamicin-induced nephrotoxicity in male ICR mice. Twelve male ICR mice were divided into four groups: normal (T0), negative (T-), 0.3 ml/20 g b.w. PSELE-treated (T1), and 0.5 ml/20 g b.w. PSELE-treated (T2). The kidneys were then extracted, weighed, and subjected to histopathological examination. Results showed that PSELE counteracts gentamicin-induced nephrotoxicity by mitigating its effect on weight and kidney tissue alterations in PSELE-treated mice (T1 and T2), with comparable results to normal (T0). The protective effects of the extract were attributed to the phytochemicals that mitigated the oxidative stress of gentamicin. In conclusion, PSELE is a potential therapeutic agent for nephrotoxicity mitigation.